Comparative study of various subpopulations of cytotoxic cells in blood and ascites from patients with ovarian carcinoma - Lukesova, Sarka; Vroblova, Vladimira; Tosner, Jindrich; Kopecky, Jindrich; Sedlakova, Iva; Čermáková, Eva; Vokurkova, Doris; Kopecky, Otakar (Contemporary oncology (Poznan, Poland), 2015)
AIM OF THE STUDY: A number of observations have indicated that the immune system plays a significant role in patients with epithelial ovarian cancer (EOC). In cases of EOC, the prognostic significance of tumour infiltrating lymphocytes has not been clearly explained yet. The aim is to determine the phenotype and activation molecules of cytotoxic T cell and NK cell subpopulations and to compare their representation in malignant ascites and peripheral blood in patients with ovarian cancer. MATERIAL AND METHODS: Cytotoxic cells taken from blood samples of the cubital vein and malignant ascites were obtained from 53 patients with EOC. Their surface and activation characteristics were determined by means of a flow cytometer. Immunophenotype multiparametric analysis of peripheral blood lymphocytes (PBLs) and tumour infiltrating lymphocytes (TILs) was carried out. RESULTS: CD3(+) T lymphocytes were the main population of TILs (75.9%) and PBLs (70.9%). The number of activating T cells was significantly higher in TILs: CD3(+)/69(+) 6.7% vs. 0.8% (p < 0.001). The representation of (CD3(-)/16(+)56(+)) NK cells in TILs was significantly higher: 11.0% vs. 5.6% (p = 0.041); likewise CD56(bright) and CD-56(bright) from CD56(+) cells were higher in TILs (both p < 0.001). The activation receptor NKG2D was present in 45.1% of TILs vs. 32.3% of PBLs (p = 0.034), but we did not find a significant difference in the numbers of CD56(+)/NKG2D(+) in TILs and PBLs. CONCLUSIONS: These results prove that the characteristics and intensity of anti-tumour responses are different in compared compartments (ascites/PBLs). The knowledge of phenotype and functions of effector cells is the basic precondition for understanding the anti-tumour immune response.
Keywords: tumour-infiltrating lymphocytes; ovarian cancer; NK cells; flow cytometry; NKG2D